Judgments of Economic Fairness Are Based More on Perceived Economic Mobility Than Perceived Inequality. (September 2020) - Heiserman, Nicholas; Simpson, Brent; Willer, Robb
Are judgments of the fairness of the American economy based on perceptions of economic inequality, mobility, or both? In two experiments, the authors varied information on levels of U.S. inequality and mobility, measuring effects on individuals' judgments of economic fairness and meritocracy. Although both treatments influenced perceptions of economic fairness and meritocracy, the mobility effect was generally larger. The two treatments did not interact, countering a common claim that high social mobility legitimizes high inequality. Effects on preferences for government action to reduce inequality and increase mobility were weak or nonexistent. Additional conditions that measured, rather than manipulated, inequality and mobility perceptions showed that respondents generally perceived inequality to be very high but were more optimistic about the level of mobility. Our studies suggest that Americans' optimism about economic mobility does more to mitigate concerns about economic fairness than does underestimation of economic inequality.